The Effectiveness of Implementing Mobile Health Applications in Cancer Patients: A Literature Review - Aprilia Dian Prawesti; La Ode Abdul Rahman (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background: Cancer is a non-communicable disease which is one of the causes of death in the world with the number of cancer patients increasing. Cancer patients are expected to be able to carry out self-management starting from diagnosis to achieving long-term care goals that require a support system from family, environment, health workers, information, and communication technology. Health applications (mHealth) have been proposed as a promising intervention modality in the health context that has the potential to improve treatment outcomes. Objectives: This review aims to analyse the effectiveness of implementing mobile health in cancer patients. Method: This review used by the author is a literature review using several databases, namely Pubmed, Cochrane Library, EbscoHost and Google Scholar from 2017 to 2022. Result: The article discussed is the application of the mHealth application in cancer patients. The results of literature reviews from several journals provide information on the benefits of using the mHealth application, especially for cancer patients related to self-management of cancer patients, information facilities and communication media for cancer patients. Conclusion: This study shows that mHealth application provide many benefits for cancer patients related to information, communication between patients and health care provider, self-management to improve the quality of life for cancer patients.